1979
DOI: 10.1111/j.1550-7408.1979.tb04651.x
|View full text |Cite
|
Sign up to set email alerts
|

Development, Ultrastructure, and Mode of Transmission of Amblyospora sp. (Microspora) in the Mosquito*

Abstract: Amblyospora sp. in Culex salinarius (Coquillett) is transovarially transmitted and has 2 developmental sequences, one in each host sex. In females, the entire life cycle is restricted to oenocytes which become greatly hypertrophied due to the multiplication of diplokaryotic cells during merogony and come to lie next to ovaries. Sporulation occurs only after a blood meal is taken and is shortly followed by infection of the oocytes and subsequent transmission to the next host generation. In the male host, infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1
7

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 14 publications
4
51
1
7
Order By: Relevance
“…The degree to which maternal-mediated transovarial transmission contributes to continual maintenance of the parasite within a mosquito population varies widely among the numerous species of Amblyospora (Kellen et al 1965, 1966, Andreadis and Hall 1979a, b, Lord et al 1981, Sweeney et al 1988. In A. connecticus, where roughly one-half of the infected female progeny develop benign infections and survive to transmit infections from one successive generation to the next, transovarial transmission can sustain the parasite for several generations in the absence of horizontal transmission.…”
Section: Evolutionary Strategies and Adaptations For Survivalmentioning
confidence: 99%
“…The degree to which maternal-mediated transovarial transmission contributes to continual maintenance of the parasite within a mosquito population varies widely among the numerous species of Amblyospora (Kellen et al 1965, 1966, Andreadis and Hall 1979a, b, Lord et al 1981, Sweeney et al 1988. In A. connecticus, where roughly one-half of the infected female progeny develop benign infections and survive to transmit infections from one successive generation to the next, transovarial transmission can sustain the parasite for several generations in the absence of horizontal transmission.…”
Section: Evolutionary Strategies and Adaptations For Survivalmentioning
confidence: 99%
“…This indicates a negative impact of A. ferocis on the reproductive capacity of P. ferox. This differed from females of Culex salinarius infected with Amblyospora salinaria Becnel et Andreadis, 1998 where there were no significant differences found in the overall fecundity of infected females but a significant reduction of 52% in egg hatch (Andreadis and Hall 1979). Edhazardia aedis (Kudo, 1930) has been reported to reduce both fecundity and egg hatch in Aedes aegypti.…”
Section: Discussionmentioning
confidence: 40%
“…The morphology and ultrastructural features of the meiospores are similar to a previous description of A. ferocis . The binucleate spores found in the ovaries of adult P. ferox are similar in morphology and ultrastructural features to other species of Amblyospora (Andreadis and Hall 1979, Andreadis 1985a, Hall and Washino 1986, Sweeney et al 1988, Becnel 1992.…”
Section: Discussionmentioning
confidence: 64%
“…Five clades of bacteria have been identified as early male-killing agents (Rickettsia, Wolbachia, Spiroplasma, Flavobacteria, and a gamma proteobacterium) (Hurst et al, 2003;Majerus, 2003). Late male killing was previously recorded only in mosquitoes and is caused by a microsporidium (Andreadis and Hall, 1979;Andreadis, 1985) but our group recently found late male killing in the oriental tea tortrix Homona magnanima (Diakonoff) collected from Ibaraki Prefecture, Japan (Morimoto et al, 2001). Morimoto et al (2001) reported that the causative agent of late male killing of H. magnanima is maternally heritable, horizontally transmissible, and microorganisms that cause other male-killing phenomena, such as Wolbachia, Spiloplasma, Rickettsia, or microsporidia, are not responsible.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of early male killing of Drosophila melanogaster, the target tissues may be the primordial mesoderm and nervous system of male embryos (Tsuchiyama et al, 1978;Koana and Miyake, 1983). In the late male killing of mosquitoes, microsporidian cells multiply in enocytes and fat body tissues in male larvae, but only in enocytes in female larvae (Andreadis and Hall, 1979;Andreadis, 1985). Infection in male larvae is lethal because of the rapid and massive multiplication of microsporidia.…”
Section: Introductionmentioning
confidence: 99%